2011
DOI: 10.4103/2230-8210.86988
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis 1 with pheochromocytoma

Abstract: Von Hippel–Lindau (VHL) disease includes a wide spectrum of highly vascular tumors like pheochromocytoma, cysts and adenomas of the pancreas and kidney, endolymphatic sac and renal cell carcinoma. Molecular analysis of the VHL gene is vital in these patients and their kindred. Neuroendocrine pancreatic tumors are rare and are known for their malignant and metastatic potential. We discuss an interesting case of a young lady who had a strong family history of central nervous system and spinal tumors. Our patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Studies have shown that almost 5–7% of NF-1 patients develop pheochromocytomas or paragangliomas in their lifetimes [ 7 ]. While the incidence rate of PHEO in NF-1 with hypertension has been reported to be as high as 20–50% [ 9 ]. We have also described a similar scenario where a patient with NF-1 and hypertension was eventually diagnosed to have a PHEO.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that almost 5–7% of NF-1 patients develop pheochromocytomas or paragangliomas in their lifetimes [ 7 ]. While the incidence rate of PHEO in NF-1 with hypertension has been reported to be as high as 20–50% [ 9 ]. We have also described a similar scenario where a patient with NF-1 and hypertension was eventually diagnosed to have a PHEO.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromatosis Type 1 (NF1) is characterised by cutaneous café-au-lait spots, Lisch nodules in the iris, freckling of the axillary and inguinal regions and multiple cutaneous neurofibromas. It is associated with phaeochromocytoma in approximately 1% of patients and GEP NETs in a similar percentage [ 15 , 25 ]. NF1 is caused by a mutation in the tumour suppressor gene NF1 , which is localised on the long arm of chromosome 17.…”
Section: Gastroenteropancreatic Neuroendocrine Tumours (Gep-nets)mentioning
confidence: 99%
“… 1 NF1 patients also have a higher predilection for developing tumors, such as pheochromocytomas, gastrointestinal stromal tumors, and paraganglionomas. 2 Pheochromocytomas, in particular, occur in only 0.1%–5.7% of patients with neurofibromatosis. 2 Therefore, there is minimal literature on the treatment and therapeutic side effects of pheochromocytomas in the context of NF1.…”
Section: Introductionmentioning
confidence: 99%